Responder
The approximate solutions are \( x \approx -0.25 \) and \( x \approx 2.5 \).
Solución
To find the approximate solutions to the equation \( f(x) = g(x) \), we will evaluate both functions \( f(x) \) and \( g(x) \) at various values of \( x \) and look for points where they are approximately equal.
### Step 1: Define the functions
- \( f(x) = x^4 + 9x^2 - 3 \)
- \( g(x) = \left(\frac{1}{2}\right)^{x-2} \)
### Step 2: Create a table of values
We will calculate \( f(x) \) and \( g(x) \) for a range of \( x \) values to find where they intersect.
Let's evaluate \( f(x) \) and \( g(x) \) for \( x \) values from -2 to 3 in increments of 0.25.
### Step 3: Calculate values
1. **For \( x = -2 \)**:
- \( f(-2) = (-2)^4 + 9(-2)^2 - 3 = 16 + 36 - 3 = 49 \)
- \( g(-2) = \left(\frac{1}{2}\right)^{-2-2} = \left(\frac{1}{2}\right)^{-4} = 16 \)
2. **For \( x = -1.75 \)**:
- \( f(-1.75) = (-1.75)^4 + 9(-1.75)^2 - 3 \approx 29.64 \)
- \( g(-1.75) = \left(\frac{1}{2}\right)^{-1.75-2} \approx 5.66 \)
3. **For \( x = -1.5 \)**:
- \( f(-1.5) = (-1.5)^4 + 9(-1.5)^2 - 3 \approx 18.69 \)
- \( g(-1.5) = \left(\frac{1}{2}\right)^{-1.5-2} \approx 3.17 \)
4. **For \( x = -1.25 \)**:
- \( f(-1.25) = (-1.25)^4 + 9(-1.25)^2 - 3 \approx 10.39 \)
- \( g(-1.25) = \left(\frac{1}{2}\right)^{-1.25-2} \approx 2.00 \)
5. **For \( x = -1 \)**:
- \( f(-1) = (-1)^4 + 9(-1)^2 - 3 = 1 + 9 - 3 = 7 \)
- \( g(-1) = \left(\frac{1}{2}\right)^{-1-2} = \left(\frac{1}{2}\right)^{-3} = 8 \)
6. **For \( x = -0.75 \)**:
- \( f(-0.75) = (-0.75)^4 + 9(-0.75)^2 - 3 \approx 2.39 \)
- \( g(-0.75) = \left(\frac{1}{2}\right)^{-0.75-2} \approx 4.00 \)
7. **For \( x = -0.5 \)**:
- \( f(-0.5) = (-0.5)^4 + 9(-0.5)^2 - 3 \approx -0.44 \)
- \( g(-0.5) = \left(\frac{1}{2}\right)^{-0.5-2} \approx 2.83 \)
8. **For \( x = 0 \)**:
- \( f(0) = 0^4 + 9(0)^2 - 3 = -3 \)
- \( g(0) = \left(\frac{1}{2}\right)^{0-2} = \frac{1}{4} = 0.25 \)
9. **For \( x = 0.5 \)**:
- \( f(0.5) = (0.5)^4 + 9(0.5)^2 - 3 \approx -1.44 \)
- \( g(0.5) = \left(\frac{1}{2}\right)^{0.5-2} \approx 1.41 \)
10. **For \( x = 1 \)**:
- \( f(1) = 1^4 + 9(1)^2 - 3 = 1 + 9 - 3 = 7 \)
- \( g(1) = \left(\frac{1}{2}\right)^{1-2} = 2 \)
11. **For \( x = 1.5 \)**:
- \( f(1.5) = (1.5)^4 + 9(1.5)^2 - 3 \approx 18.69 \)
- \( g(1.5) = \left(\frac{1}{2}\right)^{1.5-2} \approx 1.41 \)
12. **For \( x = 2 \)**:
- \( f(2) = 2^4 + 9(2)^2 - 3 = 16 + 36 - 3 = 49 \)
- \( g(2) = \left(\frac{1}{2}\right)^{2-2} = 1 \)
13. **For \( x = 2.5 \)**:
- \( f(2.5) = (2.5)^4 + 9(2.5)^2 - 3 \approx 90.06 \)
- \( g(2.5) = \left(\frac{1}{2}\right)^{2.5-2} \approx 0.707 \)
### Step 4: Analyze the results
From the calculations, we can see that:
- At \( x \approx -1 \), \( f(-1) \approx 7 \) and \( g(-1) \approx 8 \) (close).
- At \( x \approx -0.75 \), \( f(-0.75) \approx 2.39 \) and \( g(-0.75) \approx 4.00 \) (getting closer).
- At \( x \approx 0.5 \), \( f(0.5) \approx -1.44 \) and \( g(0.5) \approx 1.41 \) (crossing zero).
- At \( x \approx 1 \), \( f(1) \approx 7 \) and \( g(1) \approx 2 \) (still diverging).
### Conclusion
The approximate solutions to the equation \( f(x) = g(x
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución